Reduction in colorectal cancer incidence by screening endoscopy - Brenner, Hermann; Heisser, Thomas; Cardoso, Rafael; Hoffmeister, Michael (Nature reviews. Gastroenterology & hepatology, 2023)
Colorectal cancer (CRC) incidence rates decreased by up to 50% in older age groups in the USA in the era of the widespread uptake of screening colonoscopy, despite adverse trends in CRC risk factors and increasing CRC incidence at younger ages. However, reported first results from a randomized trial, the NordICC study, suggested rather modest effects of screening colonoscopy. As outlined in this Perspective, the apparent discrepancy between real-world and trial evidence could be explained by strong attenuation of effect estimates from screening endoscopy trials by several factors, including limited screening adherence, widespread uptake of colonoscopy outside the screening offers and the inclusion of prevalent, non-preventable CRC cases in reported numbers of incident cases. Alternative interpretations of screening endoscopy trial results accounting for prevalence bias are in line with trends in CRC incidence reduction in countries offering CRC screening, and should encourage more widespread implementation and uptake of effective CRC screening.
Online veröffentlicht: 4. Oktober 2023
Gesehen am 23.11.2023